2007
DOI: 10.1021/es070999r
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lubrication Oil in Particulate Emissions from a Hydrogen-Powered Internal Combustion Engine

Abstract: Recent studies suggest that trace metals emitted by internal combustion engines are derived mainly from combustion of lubrication oil. This hypothesis was examined by investigation of the formation of particulate matter emitted from an internal combustion engine in the absence of fuel-derived soot. Emissions from a modified CAT 3304 diesel engine fueled with hydrogen gas were characterized. The role of organic carbon and metals from lubrication oil on particle formation was investigated under selected engine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(51 citation statements)
references
References 19 publications
2
46
1
2
Order By: Relevance
“…Many results revealed that wear and (He and Bao, 2005). To overcome the limitations of plant oil, its chemicals can be modified mainly through transesterification (Forson et al, 2004;Miller et al, 2007;Ssempebwa and Carpenter, 2009;Uosukainen et al, 1998). This process reduces the number of hydrogen molecules in the beta carbon (C) position of the Calophyllum inophyllum (CI) oil substrate, thus, improving the oxidative and thermal stability of biodiesel as an important lubricity property (Makkar et al, 1997;Yunus et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Many results revealed that wear and (He and Bao, 2005). To overcome the limitations of plant oil, its chemicals can be modified mainly through transesterification (Forson et al, 2004;Miller et al, 2007;Ssempebwa and Carpenter, 2009;Uosukainen et al, 1998). This process reduces the number of hydrogen molecules in the beta carbon (C) position of the Calophyllum inophyllum (CI) oil substrate, thus, improving the oxidative and thermal stability of biodiesel as an important lubricity property (Makkar et al, 1997;Yunus et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…During engine operation, lubricating oil consumption is inevitable and this is the reason why PM emissions were found in a hydrogenpowered engine [24]. The contribution of lubricating oil to PM formation is focused primarily on soluble organic fraction (SOF) [25] and soot [26].…”
Section: Introductionmentioning
confidence: 99%
“…The particulate investigations with various fuels are based on the ethanol ratio [52][53][54][55][56], the additive allowances [57] or the aromatic content [58] in the fuel or on the soot content [7] and the additives [59,60] in the oil.…”
Section: Fuel-specific Studiesmentioning
confidence: 99%